The Secularisation of Conscience: A Natural Law Critique - Constance Youngwon Lee (Australian Journal of Law & Religion, 2024)
The modern conception of a ‘secular conscience’ is at one time, both paradoxical and reductive. This phenomenon is attributable to two main factors. In the formal sense, the problem stems from a facile or partial invocation of the term, a result of the fragmentation of its multiple referents. In a substantive sense, the loss of conscience’s explanatory power is a direct result of removing moral structures that underpin traditional formulations of the concept. Historically, conscience has been a necessary component of moral epistemologies. As the innate mechanism for moral discernment, conscience existed as a core part of practical reasoning. In this backdrop, one of secularism’s most profound implications has been to shift conscience’s emphasis away from notions of ‘higher responsibility’ to ‘individual authenticity’. To make sense of this shift, the present article begins by considering the process of ‘secularisation’. Harold Berman defines ‘secularisation’ as the steady displacement of existing normative foundations. The article goes on to trace the etymological development of conscience as a concept and its historical link to moral agency. An examination of traditional normative structures follows, as represented by two seminal accounts of conscience in Western natural law tradition, namely those of Thomas Aquinas and John Calvin. Notwithstanding the variations in emphases due to denominational differences, both these natural law accounts offer a coherent normative outlook, adequate to sustain an integrated concept of conscience. The article ultimately seeks to critique the explanatory potential of modern accounts of conscience by exposing the ontological predicates of secular-rational modalities from the natural law perspective.